A thousand heartbeats - Cass, Kiera (HarperTeen, an imprint of HarperCollinsPublishers, 2022)
"Princess Annika has lived a life of comfort--but no amount of luxuries can change the fact that her life isn't her own to control. The king, once her loving father, has gone cold, and Annika will soon be forced into a loveless marriage for political gain. Miles away, small comforts are few and far between for Lennox. He has devoted his life to the Dahrainian army, hoping to one day help them reclaim the throne that was stolen from them. For Lennox, the idea of love is merely a distraction--nothing will stand in the way of fighting for his people. But when love, against all odds, finds them both, they are bound by its call. They can't possibly be together--but the irresistible thrum of a thousand heartbeats won't let them stay apart."--